Multi Level Marketing From A Sharia Economic Perspective - Ana Siti Parida Dwi Yuliantika; Alda Maulidy; Asnah; Siva Anis Sabina (Penerbit Hellow Pustaka, 2024)
Multi-level marketing (MLM) is a business model in which a company sells products through a network of independent distributors. From a sharia economic perspective, MLM often causes debate because some of its practices can be questioned from a sharia compliance perspective. First of all, MLM emphasizes the aspect of buying and selling products, which is in line with sharia economic principles which encourage legitimate business activities and avoid usurious or speculative transactions. However, many MLMs face criticism because they tend to focus more on recruiting new members than actual product sales. This is contrary to sharia principles which emphasize justice and honesty in business. Second, in MLM, there is an element of profit sharing which is usually disproportionate between the company, distributors and network members. In sharia economics, the distribution of profits must be fair and balanced, and practices that cause injustice in the distribution of profits must be avoided.